EFEKTIVITAS PERIODISASI KEPENGURUSAN RT DAN RW BERDASARKAN PERDA KOTA TASIKMALAYA NOMOR 10 TAHUN 2007 TENTANG RUKUN TETANGGA DAN RUKUN WARGA DALAM PERSPEKTIF SIYASAH DUSTURIAH (Studi Kasus Di Kelurahan Sukamaju Kidul Kecamatan Indihiang Kota Tasikmalaya) - Noor, Fauz (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
Islamic state administration (Siyasah dusturiyah) is related to the concept of leadership, namely the periodization of the term of service or the position of a leader is something new in the siyasa dusturiyah, where in the Islamic state the boundaries of a leader's position are not limited, whereas in modern state administration, especially in Indonesia, currently there are limitations based on the time or period of good leaders on a small to large scale as outlined in the regulations set by the government. This study aims to determine the views of siyasah dusturiyah related to the periodization of the leader, the perception of the community in RT 003 RW 002 and the periodization of the head of the Rukun Tetangga. This study uses an empirical research methodology with a qualitative approach. Sources of data used are primary and secondary data. The results of this study indicate that there is a dualism of views on periodization where in the siyasa dustiriyah of a leader there is no periodization while according to the Regional Regulation there is periodization, this can be found based on rules based on the principle of benefit. The public's perception of the periodization of the head of the Rukun Tetangga is different from local regulations and tends to violate the rules. In Sukamazukidul, the periodization of the head of the RT was not effective, because many RTs did not do the periodization.